ANALISA GAYA ANGKAT DENGAN VARIASI SUDUT ELEVASI PADA SILINDER PENGANGKAT EXCAVATOR CAT 320 - Zuchry M, Muhammad (SMARTek, 2011)
Excavator usage today is widely used to help the physical work. 320 Excavator machine hasproven its ability to be supported by reliable design, sturdy construction and easy maintenance.320 Excavator with power transfer system of the machine is supported by the cylinder (boom),boom Reach (length 5673 mm), Mass boom (5200 mm), and the VA boom (5460 mm) will beanalyzed starting from the lowest to the highest position elevation angle variations that vary soget the lift cylinder reaction force (Fr) maximum lift on the cylinder.